2019
DOI: 10.1016/j.jses.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

An anatomical investigation into the blood supply of the proximal humerus: surgical considerations for rotator cuff repair

Abstract: BackgroundThe purpose of this study was to investigate the blood supply of the humeral head (HH) originating from the anterior (ACHA) and posterior circumflex humeral arteries (PCHA).MethodsFormalin preserved specimens were used to measure ACHA length, ACHA length in the bicipital groove (BG), the length of the ascending branch of the ACHA, the penetration point of the ascending branch of the ACHA at the greater tuberosity (GT), and the penetration point of the ascending branch PCHA at the GT. Fresh specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(52 citation statements)
references
References 22 publications
1
47
0
Order By: Relevance
“…Second, in clinical study of treatment for complex PHFs, no intact ACHA were found in 16 cases except 1 patient But successful fracture healing was achieved in all 17 cases [29]. Last, Natalie Keough et al emphasized the variations exist for the course of the ACHA, which suggest a more signi cant contribution from the PCHA to the epiphysis [30]. In our study, a separate origin for the ACHA and PCHA was 84.3%.…”
Section: Discussionmentioning
confidence: 44%
“…Second, in clinical study of treatment for complex PHFs, no intact ACHA were found in 16 cases except 1 patient But successful fracture healing was achieved in all 17 cases [29]. Last, Natalie Keough et al emphasized the variations exist for the course of the ACHA, which suggest a more signi cant contribution from the PCHA to the epiphysis [30]. In our study, a separate origin for the ACHA and PCHA was 84.3%.…”
Section: Discussionmentioning
confidence: 44%
“…It has also been reported that branches of the PCHA may communicate dorsally with the ACHA (de la Garza et al, 1992;Duparc et al, 2001;Gerber et al, 1990). However, these anastomotic branches were not observed in other studies (Kasai et al, 1984;Keough et al, 2019;Meyer et al, 2005).…”
Section: A Transverse Branch (De Lamentioning
confidence: 88%
“…Recently, seven variation patterns have been identified with regard to the ACHA's course towards and within the intertubercular groove (Figure 2), specifically its origin, branches and its relation to the long head of biceps tendon (Keough et al, 2019). Out of 50 cadaveric To the authors' knowledge, these variations have not been mentioned or studied before, and these variations may be of clinical importance in procedures that involve the long head of biceps tendon, such as tenotomies and tenodesis surgeries.…”
Section: Variations In the Branching Pattern Of The Achamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the proximal humerus is significantly perfused by the anterolateral ascending branch of the anterior circumflex artery (24), which runs parallel to the LHBT in the bicipital groove before forming the arcuate artery. It has been suggested that this branch of the anterior circumflex humeral artery is at risk of damage during LHBT tenotomy and tenoodesis, which may theoretically disrupt perfusion to the proximal humerus and predispose it to AVN and its associated complications (25).…”
Section: Introductionmentioning
confidence: 99%